PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY (TSTS) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SDN 028 SERUSA - Robiyah '; Mahmud Alpusari; Lazim.N ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research up on its low usufructs student studying class IV. SDN 028 Serusa. Initially, of 20 students which reach KKM just 8 person (40%). Therefore researcher applies one kooperatif's learning model type Two Stay Two Stray (TSTS) . TSTS learning model this constitutes one of kooperatif's learning type that give chance to group distributes to usufruct and information to other group. This observational type is observational action braze (PTK) one that consisting of two cycles, each cycle consisting of four steps which is planning, performing, observation and reflection. Learning peripheral and instrument is data collecting consisting of material teaches that as syllabus, learning performing plan (RPP), student job sheet (LKS), activity observation sheet learns, activity observation sheet student, and dry run problem daily i. cycle and cycle II.. Activity result learns on i. cycle 62,5% by enough categories, then increasing on appointment second becomes 79,16 % get categories well. On cycle II. appointment first increases 83,33 % by good categories, then on appointment second increases again 91,66% by good peer categories. Student activity result on meet i. cycle percentage first 58,33% get enough categories, then on second appointment 70,83% also get categories well, on cycle II. first appointment 79,16% get good peer categories, on second Cycle appointment II. also experience step-up 91,66 % by ketegori tremendously good.Key word: Kooperatif model TSTS Type, IPA Learned result